Geochemical Profiles of Deep Sediment Layers from the Kolubara District (Western Serbia): Contamination Status and Associated Risks of Heavy Metals - Milica Vidak Vasić; Milena Radomirović; Pedro M. Velasco; Nevenka Mijatović (Agronomy)
Global awareness of the harmful effects of heavy metal contamination in soil has increased significantly. Understanding the vertical distribution of oxides and elements is vital for tracing the history of potential contamination. Thus, this study focuses on deep sediment cores primarily composed of quartz and clay minerals from a small village in the western Tamnava Basin of Serbia. The aim was to assess the vertical distribution of 11 oxides and 21 elements and the ecological risks of eight heavy metals by analyzing 250 sediment samples from 18 boreholes at depths ranging from 5 to 58.5 m. Deep sediment core samples were analyzed using energy-dispersive X-ray fluorescence spectrometry (ED-XRF). Potential contamination levels were evaluated within the study area. Additionally, samples were analyzed for total carbonate and organic carbon contents and particles retained on a 0.063 mm sieve. Higher than permitted concentrations of vanadium (V), thallium (Tl), and barium (Ba) were found. Notably, this zone is located above a proposed lithium and boron mine in Gornje Nedeljice, making it crucial for monitoring efforts. Even if mining operations do not commence, examining the deep sediment layers in this rural area remains important. This study offers novel and valuable data on the concentrations of potentially toxic elements in undisturbed deep sediment, serving as a benchmark for future comparisons.